Retail Visual Stimulus and Consumer Affective Responses in Impulse Buying - Agus Sugiyanto; Toni Suhara; Faye Maya Dewi; Arsadi (CV. Muris Global Education, 2026)
This study aims to analyze the influence of visual merchandising and store atmosphere on impulse buying among merchandise store consumers at Ciputra Citra Raya Mall, Tangerang, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data were collected by distributing Likert-scale questionnaires to 100 respondents who were consumers who made transactions at merchandise stores, with a sampling technique in a population whose exact number was not identified. Data analysis was carried out using SPSS version 25 which includes validity tests, reliability tests, normality tests, partial correlation analysis, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results show that visual merchandising and store atmosphere partially have a positive and significant effect on impulse buying. In addition, both variables simultaneously also have a significant effect on impulse buying. These findings indicate that attractive visual arrangements and a comfortable store atmosphere can create emotional stimuli that encourage consumers to make spontaneous purchases. This study provides an empirical contribution to the study of retail consumer behavior and can be a basis for managerial considerations in designing marketing strategies for merchandise stores in shopping centers.